(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
Natural quartz is one of die main sources of getting a unique material - quartz glass. Wide application of quartz glass in chemical and electronic industry, aviation and cosmonautics, fibre optics and computer techniques makes it absolutely indispensable. However, industrial reserves of rock-chrystal lodes, that is die most pure source of quartz stuff with minimal mineral admixturer, are practically exhausted everywhere. All this results in usage of.low quality stuff and, thus, to significant complication of technological schemes of quartz processing and concentration, to high energy waste, high waste of inorganic acids, significant increase of industrial waste. Quartz concentrate output according to traditional technologies of lode quartz processing on Urals deposits is not more then 35%. In this turn the part of defectless transparent quartz glass when smelting from granular quartz is not more then .30%. It is evident that low efficiency of quartz industry call to new scale technological decisions. 1